2011
DOI: 10.1016/j.immuni.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Notch2 Receptor Signaling Controls Functional Differentiation of Dendritic Cells in the Spleen and Intestine

Abstract: Summary Dendritic cells (DCs) in tissues and lymphoid organs comprise distinct functional subsets that differentiate in situ from circulating progenitors. Tissue-specific signals that regulate DC subset differentiation are poorly understood. We report that DC-specific deletion of the Notch2 receptor caused a reduction of DC populations in the spleen. Within the splenic CD11b+ DC subset, Notch signaling blockade ablated a distinct population marked by high expression of the adhesion molecule Esam. The Notch-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

49
549
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(621 citation statements)
references
References 49 publications
49
549
3
2
Order By: Relevance
“…Accumulating evidence indicates that Notch signaling is crucial for the development of immune cells and for the functional differentiation of T cells (12)(13)(14)(15)(16)(17)(18)(19). Recent studies have revealed that Notch signaling also regulates the development of DCs in the spleen and intestine (20) (21,22). These data indicate that Rbpj regulates the survival of CD8 − DCs in the spleen and that Notch2 signaling controls CD11b + CD103 + DCs in the intestinal LP.…”
mentioning
confidence: 98%
“…Accumulating evidence indicates that Notch signaling is crucial for the development of immune cells and for the functional differentiation of T cells (12)(13)(14)(15)(16)(17)(18)(19). Recent studies have revealed that Notch signaling also regulates the development of DCs in the spleen and intestine (20) (21,22). These data indicate that Rbpj regulates the survival of CD8 − DCs in the spleen and that Notch2 signaling controls CD11b + CD103 + DCs in the intestinal LP.…”
mentioning
confidence: 98%
“…Gut and gut-associated lymphoid tissues also contain CD11b + CD103 + cells (Bogunovic et al, 2009;Varol et al, 2009). These migratory DC subsets also have quite unique functions (Kaplan et al, 2005;Bedoui et al, 2009;King et al, 2010;Lewis et al, 2011;Shklovskaya et al, 2011). DCs represent a rare type of leukocyte in lymphoid tissues.…”
Section: Monocyte-derived Dendritic Cells (Modcs) Become a Major DC Smentioning
confidence: 99%
“…The latter hypothesis is supported by the fact that CD11b + DCs show tissuedependent TF requirements, which may reflect a certain degree of genetic imprinting on DC precursors by the host tissue. In fact, splenic CD11b + ESAM + DCs are dependent on NOTCH2 and RELB, but not on IRF4, while the CD11b + CD103 + DCs in the gut lamina propria are dependent on NOTCH2, RELB and IRF4 [6,8,10]. In contrast, lung CD11b + DCs differentiate independently of NOTCH2 and RELB but do require IRF4 [8].…”
mentioning
confidence: 95%
“…CD8a + /CD103 + DCs are required to efficiently cross-present antigen and stimulate CD8 + T cell immunity through secretion of IL-12, thereby also promoting Th1 differentiation and underlining their crucial role in the defense against intracellular pathogens [1]. In contrast, dissecting the relationship between NLT and LT CD11b + DC populations has proven difficult: phenotypically, while spleen CD11b + DCs express CD4 and endothelial cellselective adhesion molecule (ESAM) [6], NLT CD11b + DCs do not. Ontogenetically, NLT CD11b + DCs (expressing MHC-II, CD11c and CD11b) were thought to arise from both bone marrow (BM) DC-specific progenitors and monocytes, with partial dependence on both FLT3 and the macrophage/monocyte lineage growth factor receptor, CSF-1R, for their differentiation [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation